„Alchemists, medics, scientists. Medicine over the centuries”. From collections of the Polish Academy of Science, Gdansk Library - Małgorzata Mirek (Toruńskie Studia Bibliologiczne, 2018)
On 27. February 1613 Joachim Oelhaf, medicine and anatomy profesor of the Gdańsk Academic Gymnasium, preformed the first public autopsy in Poland. On the 400. anniversary of this historically important and developmental event, the Polish Academy of Science, Gdansk Library held an exhibition, “Alchemists, medics, scientists. Medicine over the centuries”. The article presents lavishly illustrated manuscripts and incunabula which were displayed during the exhibition as well as some old prints which bring the observer closer to the achievements of ancient medics and their medieval and modern followers, many of which practiced alchemy.